(3HjGf ddQSGdI GdehSheI HGdLhGgQ GdecfhfI aiYde GdHjGfs - (3CMeO GdOefghQis; (3YHO GdQMef Hf eMeO GdUZjQ GdGNVQj, CHh RjO,J (B983 (3g` s ((3eMeO Hf Ydi Hf eMeO GdNWGHi GdMSjf GdEOQjSi GdTgjQ HGdSfhSi s)
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ gPG ddQSGdI GdehSheI hSejJg MdjI GddH s
(3BNQgG (B:s
(3hGdbQhf LeY bQf hgh eGFI SfI hJeGe fUag NeShf s
(3GdfSNI HgG MhGTs
(3Je JCdjag Sfg (B950s
(3SbWJ HYV CLRGA GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdHdGZIs